It is a long way from words to action: On the integrated management of the water in Peru - Guevara Gil, Armando (2019)
The aim of this paper is to study the effectiveness of the integrated waterresources management (IWRM) principle, included in the Law Nº29338 of 2009, in three hydrological Peruvian landscapes: the aquifer of Ica-Villacurí, the upper basin of the Tambo-Ica River (Huancavelica), and the Olmos watering (Lambayeque). The analysis consists in a review of the context on water resources challenges for the country and the world and an appraisal of the advancement of IWRM in the current water management Peruvian legal framework. Also, considering James Scott anthropological perspective on “governmental failed schemes” we discuss the little effectiveness of IWRM principle in these three hydrological landscapes.